Enrollee Characteristics in an Intensive Tobacco Dependence Treatment Program: The Relationship of Race and Sex to Demographic Factors and Tobacco Use Patterns - Payne, Thomas J.; Sheffer, Christine E.; Gaughf, Natalie W.; Sutton, Monica J.; Peeples, Holly H.; Elci, Okan U.; Ma, Jennie Z.; Penman, Alan; Crews, Karen M. (Frontiers in Psychiatry, 2019)
Intensive tobacco treatment programs offer many advantages relative to other treatment options, particularly for more complex patients, e.g., highly nicotine dependent, or those with medical and psychiatric symptoms and disorders. Efforts to better understand those who choose to enroll in these programs, particularly regarding the characteristics they possess known to mediate outcomes, are important considerations in tailoring available services. In this study, we examined how participants differed key descriptive and tobacco use variables within race (African-American, Caucasian) and sex subgroups. Baseline characteristics from a large group of consecutive program enrollees were examined across targeted subgroups. Strong racial effects and some sex effects were noted for marital status, education, employment and health insurance status, alcohol consumption, presence of medical and psychiatric disorders, as well as participant tobacco use and that of family, friends and coworkers. The differences in participant tobacco use measures across race and sex factors remained significant after adjusting for the confounding effects of all other covariates. These findings have implications for characterizing key patient subgroups who present at tobacco treatment clinics. Such information may contribute to options for tailoring treatment regimens.